The Effects of the Nutrition Lottery Draw Game to Increase Nutrition Knowledge - Iman Jaladri; Martinus Ginting; Sudarto Sudarto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
A good generation must be created through effort and real work. One generation is a group of schoolchildren who are the nation's investment. A complete generation must be supported by good nutrition. In order to fulfill good food ingredients, of course, it requires proper nutritional knowledge. This study aims to determine the effect of the nutrition lottery draw game media on increasing nutritional knowledge in elementary school children. The research design used a quasi-experimental design (Non-Randomized group pre-test post-test) with research subjects of as many as 48 children divided into 2 (two) treatment groups (each group consisting of 24 people). The subjects of the study employed the students in Elementary School 17 and 20 Siantan, Jungkat District, Mempawah Regency in March 2021. Data analysis with Wilcoxon test and Man-Whithney. Furthermore, the intervention was carried out for one month effectively and divided into 2 (two) groups, namely, one group was provided games treatment and one group had no treatment. There were differences in knowledge scores before and after the intervention in the control and treatment groups. There was no difference in the increase of knowledge scores in the treatment and control groups. Keywords: Games, Nutritional Knowledge, Schoolchildren